The Relative Importance of the Various Tending Operations on the Early Growth and Survival of Sal Seedlings in Eastern Terai Sal - Rajkhowa, S. (Indian Forester, 1964)
An experiment was laid out in Eastern Terai Sal in Assam to study the effects of spacing of mother trees, rain weeding and winter treatment on the growth and survival of sal seedlings in the first three years of life. More than one rain weeding did not make any significant difference in survival of sal seedlings at any time. In the first year, clean weeding in winter and removal of weeds from the plots gave significantly better survival, but on subsequent years, the effects of winter treatments was not significant when late fires were prevented. The spacing of mother trees had an effect on survival in the first year, and in establishment of seedlings. For survival in the first year, the best spacing of mother trees was 120 ft. As for getting the seedlings established, the effect of the number of rain weeding was highly significant. In this case, all two factor and three factor interactions were significant or nearly so. The best spacing of mother trees for getting the seedlings estahlished was 90 ft.